Peningkatan Kemandirian Ekonomi Karang Taruna Desa Burai Kecamatan Tanjung Batu Ogan Ilir dengan Teknologi Bioflok dalam Membudidayakan Ikan Lele - Khusnul Khotimah SP., M.Si.; Helmizuryani; Harniatun Iswarini (Altifani Journal: International Journal of Community Engagement, 2025)
This community service initiative, conducted under the Community-Based Empowerment Scheme, aims to enhance the economic independence of the Burai Village Youth Organization (Karang Taruna) through the implementation of biofloc technology in catfish cultivation and the utilization of maggots (Black Soldier Fly larvae) as an alternative feed source. The program was carried out from March to November 2025, comprising several stages: initial exploration, Focus Group Discussions (FGDs), outreach, technical training, and field practice. The training focused on three key aspects: (1) biofloc-based catfish farming, (2) maggot cultivation as a high-protein feed, and (3) basic marketing and bookkeeping strategies. The outcomes showed a significant improvement in the capacity of village youth to manage productive, fisheries-based enterprises. However, challenges remained, including fish mortality rates of up to 30% due to unstable water quality and maggot mortality caused by high environmental temperatures. Corrective measures were implemented through regular water quality monitoring, improved feed management, and better control of maggot rearing conditions. Overall, this program successfully strengthened the technical and managerial skills of Karang Taruna members, fostered an entrepreneurial mindset, and opened up sustainable business opportunities utilizing local resources.